Further advances in understanding and optimising beam dynamics in the Diamond storage ring - Martin, I; Bartolini, R; Fielder, RT; Longhi, E; Singh, B (European Physical Society Accelerator Group (EPS-AG), 2008)
We report the results of recent beam dynamics studies of the Diamond storage ring. These studies were aimed at both improving our understanding of the machine operation as well as establishing a reliable, well corrected lattice with long lifetime and high injection efficiency suitable for later top-up operation. Particular attention has been given to measuring and controlling the linear optics of the lattice, to determining the various contributions to the overall beam lifetime and to optimising the sextupole strengths for good on and off momentum dynamic aperture. For each topic, detailed comparisons with model predictions are also described.